Is Preoperative Pyuria Associated with Postoperative Febrile Complication after Ureteroscopic Ureter or Renal Stone Removal? - Seungsoo Lee (Urogenital Tract Infection, 2020)
Purpose The association between preoperative pyuria and postoperative febrile complications after ureteroscopic ureter or renal stone removal was examined. Materials and Methods From June 2014 to July 2016, 110 patients who underwent ureteroscopic ureter or renal stone removal by a single surgeon were evaluated. The patients were categorized as the “pyuria group” and “nonpyuria group.” The sex, age, stone laterality, stone location, stone size, preoperative urine culture results, and postoperative complications in each group were analyzed. Results The pyuria and nonpyuria groups were comprised of 55 patients each. The mean ages the pyuria and nonpyuria groups were 58.4±16.1 years and 54.4±13.2 years, respectively. There were respectively, 43 and 12 unilateral and bilateral stones in the pyuria group, and 53 and two in the nonpyuria group. The stone sizes of the pyuria and nonpyuria groups were 13.1±5.4 mm and 11.1±4.7 mm, respectively. The pyuria group contained more patients with bilateral stones and larger stones than the nonpyuria group. Five and two postoperative febrile complications were encountered in the pyuria group and the nonpyuria group, respectively. No significant difference in febrile complications was observed between the two groups. In logistic regression analysis, bilateral stones and larger stones were associated with pyuria. Conclusions In ureteroscopic stone removal surgery, preoperative pyuria was associated with bilateral and larger stones, but there were no associations with febrile complications.